Every breath you take : a novel - McNaught, Judith (New York : Ballantine Books, 2005)
On wealthy philanthropist Cecil Wyatt's eightieth birthday, all the money in the world won't bring back his missing grandson, William Wyatt. The family, the police and the media all have tried in vain to discover the young man's fate. Now suspicion has turned shockingly toward William's own half-brother, the rather distant and enigmatic Mitchell Wyatt. Kate Donovan is tagged as a suspect in a high-society murder case, after a chance romantic encounter on a tropical island paradise with Mitchell Wyatt.
Keywords: Rich people -- Fiction; Murder -- Investigation -- Fiction; Man-woman relationships -- Fiction; Suspense fiction; Love stories